2022
DOI: 10.3390/brainsci12121618
|View full text |Cite
|
Sign up to set email alerts
|

Explaining L2 Lexical Learning in Multiple Scenarios: Cross-Situational Word Learning in L1 Mandarin L2 English Speakers

Abstract: Adults commonly struggle with perceiving and recognizing the sounds and words of a second language (L2), especially when the L2 sounds do not have a counterpart in the learner’s first language (L1). We examined how L1 Mandarin L2 English speakers learned pseudo English words within a cross-situational word learning (CSWL) task previously presented to monolingual English and bilingual Mandarin-English speakers. CSWL is ambiguous because participants are not provided with direct mappings of words and object refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…However, in specific circumstances, IDS may inhibit rather than facilitate learning. For example, we found that IDS negatively impacted CSWL of English words in L2 learners with a native tonal language background (Escudero et al., 2022). We have suggested that the pitch variations inherent in IDS may lead a speaker of a tonal language such as Mandarin or Thai to perceive one phonological contrast as multiple contrasts, which impacts their performance in the CSWL task.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, in specific circumstances, IDS may inhibit rather than facilitate learning. For example, we found that IDS negatively impacted CSWL of English words in L2 learners with a native tonal language background (Escudero et al., 2022). We have suggested that the pitch variations inherent in IDS may lead a speaker of a tonal language such as Mandarin or Thai to perceive one phonological contrast as multiple contrasts, which impacts their performance in the CSWL task.…”
Section: Discussionmentioning
confidence: 95%
“…In recent studies, however, minimal pairs have been included to test statistical word learning of word pairs with phonological overlap, where words differ only in their vowels (e.g., DIT-DEET) or their consonants (e.g., BON-TON). The use of minimal and nonminimal pairs in CSWL tasks has been helpful in testing whether performance in CSWL tasks is affected by the phonological contrast in the words as proposed by the Second Language Linguistic Perception model (Escudero, 2005;Escudero et al, 2022;van Leussen & Escudero, 2015). For example, Escudero et al (2016a) found that adults were able to track word-object co-occurrences across trials, thereby learning nonminimal pairs as well as vowel and consonant minimal pairs, but that performance was lowest for vowel minimal pairs.…”
Section: The Use Of Minimal and Nonminimal Pairs In Cross-situational...mentioning
confidence: 99%
“…Noisy child data are a typical example of complex data sets, with small or unbalanced samples, which yield low statistical power using conventional statistics ( Van de Schoot et al, 2017 , 2021 ; Escudero et al, 2020 ). A similar Bayesian approach has been used in many recent papers to handle complex data sets (e.g., Smit et al, 2019 , 2022 ; Escudero et al, 2020 , 2022a , 2022b ; Milne and Herff, 2020 ).…”
Section: Analyses and Resultsmentioning
confidence: 99%
“…Although current L2 models primarily focus on segmental categories, prosodic factors are also necessary to fully account for L2 speech acquisition. There have been a few attempts to expand the models' predictions to prosodic factors such as lexical tone (Chen, Best, & Antoniou, 2020;Escudero, Smit, & Mulak, 2022;Hao, 2014), which should be further pursued. The application of the ToBI framework to L2 speech, though having a long way to go, can also open up new avenues for future research.…”
Section: Temporal Implementationmentioning
confidence: 99%